2016
DOI: 10.1080/09349847.2016.1157660
|View full text |Cite
|
Sign up to set email alerts
|

Phased Array Ultrasonic Testing for Post-Weld and OnLine Detection of Friction Stir Welding Defects

Abstract: Non-destructive evaluation (NDE) techniques of phased array ultrasonic testing (PAUT) and digital x-ray radiography were employed on friction stir (FS) welded Aluminum Alloy (AA) 2219-T87 specimens. PAUT intricacies are discussed which are required for scanning of FS welded specimens with a 10 MHz 32-element transducer. The "time corrected gain" (TCG) calibration is required for scanning with an increase in index offset to compensate for decrease in A-Scan signal peak amplitude. Calibration techniques to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…(8a and b). The 2. results showed that the overall contrast in the image improved, and the dynamic range of the pixel gray value expanded, which enhanced the overall contrast of the image. Binarization threshold was selected by using Otsu's method for Fig.…”
Section: Edge Detection Of 2d Gray Image For Weld Defectsmentioning
confidence: 76%
“…(8a and b). The 2. results showed that the overall contrast in the image improved, and the dynamic range of the pixel gray value expanded, which enhanced the overall contrast of the image. Binarization threshold was selected by using Otsu's method for Fig.…”
Section: Edge Detection Of 2d Gray Image For Weld Defectsmentioning
confidence: 76%
“…Lack of penetration, tunnel formation, formation of voids, lack of fusion, surface grooves and kissing bonds are various other defects formed during Friction Stir Welding process [6]. Huggett et al [7] used Nondestructive evaluation (NDE) techniques of phased array ultrasonic testing (PAUT) and digital Xray radiography for detecting the defects in Friction Stir welded Aluminum Alloy 2219-T87 specimens. Chen et al [8] investigated about the welding defects in Friction Stir Welded Aluminum alloy 5456 joints with the help of optical microscopy (OM), energy-dispersive X-ray spectroscopy (EDS) and scanning electron microscope (SEM).…”
Section: Introductionmentioning
confidence: 99%
“…17,[23][24][25][26][27][28][29] It was also suggested that the peak temperature had to be within 80-90% of the solidus temperature of the alloy to avoid the void formation. 25 Diverse experimental studies such as ultrasonic 30 and radiographic 31 detections of voids and theoretical analysis of forces 26,32,33 were undertaken to understand the origin of void formation. Although progress made in the previous work to identify the important variables such as temperature, strain rate, torque, and maximum shear stress on the pin that affect the void formation, no rigorous mechanistic explanation, or criterion for the void formation have emerged.…”
Section: Introductionmentioning
confidence: 99%